THE USE OF CROSSWORD PUZZLE GAME TO IMPROVE STUDENT’S VOCABULARY MASTERY AT CLASS VIII OF SMP SWASTA MUHAMMADIYAH 15 KUTACANE ACADEMIC YEAR 2023/2024 - Lulu Lilian Shania; Sabrun Jamil; Putri Ayumi (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This study deals with the used crossword puzzle game to improve student’s vocabulary at class VIII SMPS Muhammadiyah 15 Kutacane Academic Year 2023/2024. Its objective is to find out whether the used crossword puzzle game has a significance effect in vocabulary . Population used in this study of class VIII were 25 and samples used in this study were 25 students. The method used in this study is an experimental method with a one group as test design .This study was carried on using quantities method. The data was analysed by using t-test. Researcher find mark t test count amounting to 8,75 Furthermore consulted with t table value on level significant 5 % with db= N -1= 25-1= 24, then obtained t table value = 1,96. So with so t count > t table or 8,52>1,96 then hypothesis accepted. With the mode obtained being a value of 88 which was the most obtained by 9 students in class VIII.Based on the data from the test results on the ability to increase vocabulary and if it is related to the KKM score for English subjects for junior high school = 65. So the students' ability to increase vocabulary through crossword puzzle game is included in the good category. Thus, from the results of the hypothesis testing above, it can be concluded that there is the use of crossword puzzle game file to student vocabulary abilities at class VIII SMPS Muhammadiyah 15 kutacane Academic Year 2023/2024.